Development of a polysaccharide-based hydrogel drug delivery system (DDS): An update - Pushpamalar, Janarthanan; Puviarasi, M.; Tan, Hui Li; Nuraina, A. D.; Ooi, L. T.; Bibi Noorheen, H. M. N.; Raahilah, Z. E.; Shameli, Kamyar; Teow, Sin Yeang * (MDPI, 2021)
Delivering a drug to the target site with minimal-to-no off-target cytotoxicity is the major determinant for the success of disease therapy. While the therapeutic efficacy and cytotoxicity of the drug play the main roles, the use of a suitable drug delivery system (DDS) is important to protect the drug along the administration route and release it at the desired target site. Polysaccharides have been extensively studied as a biomaterial for DDS development due to their high biocompatibility. More usefully, polysaccharides can be crosslinked with various molecules such as micro/nanoparticles and hydrogels to form a modified DDS. According to IUPAC, hydrogel is defined as the structure and processing of sols, gels, networks and inorganic–organic hybrids. This 3D network which often consists of a hydrophilic polymer can drastically improve the physical and chemical properties of DDS to increase the biodegradability and bioavailability of the carrier drugs. The advancement of nanotechnology also allows the construction of hydrogel DDS with enhanced functionalities such as stimuli-responsiveness, target specificity, sustained drug release, and therapeutic efficacy. This review provides a current update on the use of hydrogel DDS derived from polysaccharide-based materials in delivering various therapeutic molecules and drugs. We also highlighted the factors that affect the efficacy of these DDS and the current challenges of developing them for clinical use.